2017
DOI: 10.1177/0033354917709779
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Influenza Surveillance Using Telephone Triage and Electronic Syndromic Surveillance in the Department of Veterans Affairs, 2011-2015

Abstract: Telephone triage (TT) is a method whereby medical professionals speak by telephone to patients to assess their symptoms or health concerns and offer advice. These services are often administered through an electronic TT system, which guides TT professionals during the encounter through the use of structured protocols and algorithms to help determine the severity of the patients' health issue and refer them to appropriate care. TT is also an emerging data source for public health surveillance of infectious and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…( n = 1,065,628) with less population. Lucero-Obusan et al also reported in a study of the Department of Veterans' Affairs in the United States that telephone triage data and influenza-related indicators were significantly correlated [21]. In the present study, we used a linear regression model in which the number of telephone triages for fever and seasonality as defined by the week number were input as covariates.…”
Section: Characteristicmentioning
confidence: 95%
See 1 more Smart Citation
“…( n = 1,065,628) with less population. Lucero-Obusan et al also reported in a study of the Department of Veterans' Affairs in the United States that telephone triage data and influenza-related indicators were significantly correlated [21]. In the present study, we used a linear regression model in which the number of telephone triages for fever and seasonality as defined by the week number were input as covariates.…”
Section: Characteristicmentioning
confidence: 95%
“…There are 97 different protocols of telephone triage for chief complaints in Japan, and the urgency of the client is determined by selecting the signs and symptoms related to each chief complaint. As with telephone triage service in the departments of veterans’ affairs in the United States [ 21 ], Canada and United Kingdom [ 22 24 ], the telephone service in Osaka provides the client necessary services such as ambulance dispatch and guidance of medical institutions based on the result of the urgency [ 25 ]. The software records the sex and age group of the client, the time when the telephone triage was started and ended, the chief complaint and selected signs and symptoms, the urgency of the client and whether an ambulance was dispatched.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have predicted the number of patients with influenza-like disease and respiratory disease using telephone triage data and the number of patients visiting the emergency room [3,6,[19][20][21][24][25][26][27]. Perry and colleagues compared the prediction performance of the number of patients with respiratory disease visiting the emergency room using N4SID (numerical methods for subspace state space identification), EWMA (exponentially weighted moving average), FOS (fast orthogonal search), and a regression model [7].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they revealed that the FOS model had better prediction accuracy than the regression model if the population was large, but the regression model had the highest prediction accuracy in areas with less population. Lucero-Obusan et al also reported in a study of the Department of Veteran Affairs in the United States that telephone triage data and influenza-related indicators were significantly correlated [19]. In this study, we used a linear regression model in which the number of telephone triages for fever and seasonality as defined by the week number were input as covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation